2019
DOI: 10.2151/sola.2019-025
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Diurnal Pulses Observed in Typhoon Atsani Using Retrieved Cloud Property Data

Abstract: Using several cloud properties retrieved from the Himawari-8 satellite, combined with the best track storm center information, the temporal-spatial features of tropical cyclone (TC) diurnal pulses in 2015 Super Typhoon Atsani (T1516) are coherently depicted. To demonstrate the radially outward transition processes of the diurnal pulses from one cloud type to another, we divided high clouds into three types: opaque high cloud (OHC), cirrostratus (Cs), and cirrus (Ci). Two alternatively appeared peaks in cloud t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Numerous previous studies have pointed out that cirrus cloud coverage associated with TCs shows a diurnal cycle (e.g., Browner et al 1977;Muramatsu 1983;Lajoie and Butterworth 1984;Kossin 2002;Dunion et al 2014;Wang et al 2019). Using infrared imagery archive of TCs, Kossin (2002) found that diurnal oscillation of the cirrus canopy was evident over 300 km from the center of TCs, although it was weak near the storm center.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous previous studies have pointed out that cirrus cloud coverage associated with TCs shows a diurnal cycle (e.g., Browner et al 1977;Muramatsu 1983;Lajoie and Butterworth 1984;Kossin 2002;Dunion et al 2014;Wang et al 2019). Using infrared imagery archive of TCs, Kossin (2002) found that diurnal oscillation of the cirrus canopy was evident over 300 km from the center of TCs, although it was weak near the storm center.…”
Section: Introductionmentioning
confidence: 98%